Epistemologia, ontologia e linguagem em verdade e método: uma exposição crítica - Fanton, Marcos (2015)
The main purpose of this paper is to carry out a critical assessment of Gadamer's philosophical hermeneutics. To achieve this objective, in a first moment, a reconstruction of the main theses developed in Truth and Method in order to clarify the philosophical position, the theoretical status and the main object of philosophical hermeneutics. In a second moment, however, we will make some critical comments about the philosophical hermeneutics‟ program exposed above, pointing to possible inaccuracies and a self-contradiction. Such problems arise, as it will be argued, from a confusion between different theoretical dimensions of language that goes unnoticed by Gadamer.